Pemenuhan Hak Nafkah dan Keharmonisan Keluarga pada Pasangan Santri yang Menikah Saat Menempuh Pendidikan di Pondok Pesantren Darul Ulum Kandangan - sahibul ardi; Huzaimah (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Marriage is both a religious obligation and the only religiously sanctioned means of fulfilling sexual needs. Beyond meeting biological needs, marriage entails mutual responsibilities, including the husband's obligation to provide financial support and the shared responsibility of maintaining family harmony. This study examines married student couples in the Darul Ulum Islamic Boarding School, Kandangan, who continue their education after marriage. Using a qualitative case study approach, data were collected through interviews, observations, and documentation and analyzed inductively. The findings reveal that household economic needs are met through a combination of family support and the couples' independent efforts, reflecting Islamic values of family solidarity and productive work. Family relationships were generally harmonious despite the challenges of balancing marital responsibilities with ongoing educational commitments. The study concludes that married student couples face dual demands in managing family life while pursuing their education.